Evaluación Del Régimen Tributario Sobre El Crecimiento De Las Empresas Del Sector Automotriz En Colombia (2025)
Over the past five years, the Colombian economy has faced a series of challenges, including the crisis and recovery from the COVID-19 pandemic. This has allowed tax policies to be an essential point on political agendas, since the reforms and problems associated with them have caused impacts among various economic sectors.